Are Fireworms Venomous? Evidence for the Convergent Evolution of Toxin Homologs in Three Species of Fireworms (Annelida, Amphinomidae). (23rd December 2017) - Verdes, Aida; Simpson, Danny; Holford, Mandë
Abstract: Amphinomids, more commonly known as fireworms, are a basal lineage of marine annelids characterized by the presence of defensive dorsal calcareous chaetae, which break off upon contact. It has long been hypothesized that amphinomids are venomous and use the chaetae to inject a toxic substance. However, studies investigating fireworm venom from a morphological or molecular perspective are scarce and no venom gland has been identified to date, nor any toxin characterized at the molecular level. To investigate this question, we analyzed the transcriptomes of three species of fireworms— Eurythoe complanata, Hermodice carunculata, and Paramphinome jeffreysii —following a venomics approach to identify putative venom compounds. Our venomics pipeline involved de novo transcriptome assembly, open reading frame, and signal sequence prediction, followed by three different homology search strategies: BLAST, HMMER sequence, and HMMER domain. Following this pipeline, we identified 34 clusters of orthologous genes, representing 13 known toxin classes that have been repeatedly recruited into animal venoms. Specifically, the three species share a similar toxin profile with C-type lectins, peptidases, metalloproteinases, spider toxins, and CAP proteins found among the most highly expressed toxin homologs. Despite their great diversity, the putative toxins identified are predominantly involved in three major biological processes: hemostasis, inflammatory response, and allergic reactions, all of which are commonly disrupted after fireworm stings. Although the putative fireworm toxins identified here need to be further validated, our results strongly suggest that fireworms are venomous animals that use a complex mixture of toxins for defense against predators.